Aspects of style, form and harmony in the sacred music of Heinrich Schutz, with specific reference to his Psalms of David and Geistliche Chormusik - Lambert, Peter Bernard (Not Specified, 2023)
In this dissertation, the sacred music of Schutz is discussed within the context of his contribution as a church composer during the period when music was experiencing the gradual transition from the renaissance to the baroque. Schutz assimilated the principles of composition which characterised the late renaissance and applied them in a manner which at the same time reflected his own progressive approach to these established principles. This progressive nature enabled him to introduce the Italian style recitativo in Germany for the first time, and it made him receptive to the use of the monodic style, which he also absorbed in Italy. He assumed an important role as a Protestant composer and considered it of fundamental importance to expound the meaning, and thereby realize the aims, of the sacred text when set to music. His Lutheran background influenced his choice of text sources as well as his extensive use of the vernacular for his sacred music. Examples from his Psalms of David as well as the Geistliche Chom1usik, are used to illustrate aspects of his contribution to music in Germany, and to music in general.